Assistance in the Publication of Activity Information Via Instagram Media at Jasdam II/Sriwijaya - Nur It'snaini, Aliyah Zahrah; Lexianingrum, Siti Rahayu Pratami; Misnawati, Desy; Hafizni, Mohammad (Jurnal Pengabdian Pancasila (JPP), 2023)
Publication of activity information via Instagram media is an alternative form of improving the good image of Jasdam II Sriwijaya in the public eye with the aim of this community service activity being able to introduce Jasdam II Sriwijaya in detail with Instagram visuals packaged in an attractive way. The community service method is carried out by mentoring which is structured in three stages, namely 1) preparation, 2) implementation and 3) evaluation. The subject of service is the public relations manager of Jasdam II Sriwijaya. The results obtained were a 100% increase in the knowledge of public relations managers at Jasdam II Sriwijaya, not only in terms of visits but from followers, impressions, likes and viewers of the Jasdam II/SWJ instastory. After carrying out this community service activity, the community service team had a positive impact in introducing the community.